Film and Everyday Eco-disasters - Murray, Robin L.; Heumann, Joseph K. (Book collections on Project MUSE., 2014)
Eco-disasters such as coal-mining accidents, oil spills, and food-borne diseases appear regularly in the news, making them seem nearly commonplace. These ecological crises highlight the continual tensions between human needs and the environmental impact these needs produce. Contemporary documentaries and feature films explore environmental-human conflicts by depicting the consequences of our overconsumption and dependence on nonrenewable energy. Film and Everyday Eco-disasters examines changing perspectives toward everyday eco-disasters as reflected in the work of filmmakers from the silent era forward, with an emphasis on recent films such as Dead Ahead, an HBO dramatization of the Exxon Valdez disaster; Total Recall, a science fiction action film highlighting oxygen as a commodity; The Devil Wears Prada, a comment on the fashion industry; and Food, Inc., a documentary interrogation of the food industry. The authors evaluate not only the success of these films as rhetorical arguments but also their rhetorical strategies. This interdisciplinary approach to film studies fuses cultural, economic, and literary critiques in articulating an approach to ecology that points to sustainable development as an alternative to resource exploitations and their associated everyday eco-disasters. --Provided by publisher.